Topsy and Tim play football - Adamson;Jean (London Ladybird, 2010)
Topsy and Tim are always finding fun adventures in the real world, and this story is reassuring for young children having first experiences of their own. Topsy and Tim join the local football club. Along with their friends, they practice their skills, including dribbling a ball around cones. Then they play a proper game. It's so much fun that Topsy and Tim want to play football every day! Children who are starting to be interested in football will love to read about all the details of the club."